Unraveling the role of mobile genetic elements in antibiotic resistance transmission and defense strategies in bacteria - Ranjith Kumavath; Puja Gupta; Eswar Rao Tatta; Mahima S. Mohan; Simi Asma Salim; Siddhardha Busi (Frontiers in Systems Biology)
Irrational antibiotic use contributes to the development of antibiotic resistance in bacteria, which is a major cause of healthcare-associated infections globally. Molecular research has shown that multiple resistance frequently develops from the uptake of pre-existing resistance genes, which are subsequently intensified under selective pressures. Resistant genes spread and are acquired through mobile genetic elements which are essential for facilitating horizontal gene transfer. MGEs have been identified as carriers of genetic material and are a significant player in evolutionary processes. These include insertion sequences, transposons, integrative and conjugative elements, plasmids, and genomic islands, all of which can transfer between and within DNA molecules. With an emphasis on pathogenic bacteria, this review highlights the salient features of the MGEs that contribute to the development and spread of antibiotic resistance. MGEs carry non-essential genes, including AMR and virulence genes, which can enhance the adaptability and fitness of their bacterial hosts. These elements employ evolutionary strategies to facilitate their replication and dissemination, thus enabling survival without positive selection for the harboring of beneficial genes.